Strategy faLearning Strategies at SD Muhammadiyah Wringinanom during the Covid 19 Pandemic or SD Muhammadiyah Wringinanom in Learning during the Covid-19 Pandemic - Devi Nur Amin Putriningsih; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The covid-19 pandemic has affected various fields, one of which is also in the field of education. Education is one of the factors that has been greatly affected by the Covid-19 outbreak. The government and educators are doing their best so that education can run well even with a pandemic like this. During the Covid-19 pandemic, the government established Distance Education. Distance learning is an effort so that learning can be carried out properly even though it uses a different system. With the implementation of distance learning, teachers are required to be more able to master technology and be creative in designing distance learning so that it can always run effectively. However, in this distance learning is also inseparable from the advantages and disadvantages in its implementation. Thus distance learning is applied to break the chain of spreading the Covid-19. SD Muhammadiyah Wringinanom provides programs that can assist students' distance learning by implementing one of the online system learning programs.